Brand Image in Cosmetic Packaging Design with a Visual Appeal Approach (Case Study: MS Glow) - Devi, Ni Made Chandra Oktavia; Julianto, I Nyoman Larry; Swandi, I Wayan (Universitas Ciputra, 2024)
The study identified the brand image of the cosmetic packaging moisturizer MS Glow. MS Glows is a local cosmetics brand in Indonesia, one of its best products is Moisturizers which won the first championship as the best local moisturizer of the year 2022. Qualitative descriptive methods with observation techniques, literature, and documentation are used in this research. The theoretical framework used included a visual appeal approach (Kotler and Amstrong) and brand image (Keller). The results showed that the moisturizer packaging of three variants (yuzu, watermelon, cactus, and grape seed) consists of primary, secondary, and tertiary packaging. Practical shapes, lightweight materials, colors in harmony with product variants, a combination of serif and sans serif letters, illustrations highlighting the main materials, and an asymmetrical layout. Three brand image components, namely the strength of the brand association, the benefits of its association, and the uniqueness of brand associations evaluate the ideal and accurate design of the MS Glow moisturizer packaging so that products spread across the market can be trusted. This study shows that an ideal visual appeal can build relevant packaging and open up opportunities for MS Glow to create products with their distinctive image.